Decomposiç\~ao estrutural do consumo de energia elétrica no Brasil - Mário Jorge Mendonça; Amaro Olimpio Pereira; Rodrigo R. de Bragança Aylmer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The goal of this paper is to identity the sectors with the greatest potential to contribute to reducing electricity consumption. To this end, we apply the analysis consumption multiplier and the structural decomposition on the hybrid Input-Output Matrix between which combines data from the National Energy Balance and the National Accounts, are performed. The results for the period 2015-2018 show that many sectors had significant energy efficiency gains. It can also be noted that the implementation of energy efficiency measures today may be more complex than it was in 2001. The transport sector has a relevant connection of electrical consumption with the service and energy sectors, and has a higher multiplier energy demand. Priority for efficiency measures should be given to the Other Industries, Pulp and Paper and Agriculture sectors. Special attention should also be given to the Mining and Pelletizing, Non-metallic Minerals, Aluminum Industry (non-ferrous) and Steel Industry (steel and derivatives) sectors.
Keywords: C67; D57; C80; 330; rationing; hybrid input-output matrix; energy intensity; structural decomposition and multiplier effect